2017
DOI: 10.2460/javma.251.5.566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patient-specific porous titanium endoprostheses in dogs with tumors of the mandible, radius, or tibia: 12 cases (2013–2016)

Abstract: OBJECTIVE To characterize the processes involved in and outcomes achieved with custom-designed patient-specific implants to provide functional replacement of skeletal structures in dogs with tumors of the mandible, radius, or tibia. DESIGN Prospective case series. ANIMALS 6 dogs with mandibular tumors, 5 with tumors of the distal aspect of the radius, and 1 with a tumor in the distal aspect of the tibia treated from June 2013 to September 2016 at 3 referral centers. PROCEDURES After tumor staging, implants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…It became apparent that this was an unrealistic expectation. In one veterinary study, a delay of up to 4 weeks was reported from the time of original examination for implant design to surgery . In a case report of a cat, the time between planning CT and surgery was 4 weeks but could have been shorter if it were not for customs and border issues .…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…It became apparent that this was an unrealistic expectation. In one veterinary study, a delay of up to 4 weeks was reported from the time of original examination for implant design to surgery . In a case report of a cat, the time between planning CT and surgery was 4 weeks but could have been shorter if it were not for customs and border issues .…”
Section: Discussionsupporting
confidence: 76%
“…After acquisition of the planning CT study, the surgeon evaluated the tumour with a radiologist and determined the proximal extent of the tumour in the radius. The site of the radial osteotomy was determined by adding 4.5 to 5.0 cm proximal to the most proximal extent of the tumour . The site was marked with a line on a sagittal image of the limb and saved as a JPEG file.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations